1989
DOI: 10.1021/ie00091a008
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature sulfidation-regeneration of copper(II) oxide-alumina sorbents

Abstract: Thermogravimetric analysis (TGA) and flow-reactor experiments were used to study sulfidationregeneration of highly porous Cu0-A1203 sorbents. In TGA studies, sulfidation of reduced sorbents produced a high-temperature form of digenite (Cu9+xS5) as the major crystalline product. When a platinum pan was used in the TGA, significant sulfur chemisorption on alumina occurred. Sulfur chemisorption on alumina was eliminated by use of a quartz sample pan. Reaction of the mixed-oxide sorbents with a mixture of H2S, H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 13 publications
5
49
0
Order By: Relevance
“…58 Because of the apparent limitations of the zinc ferrite sorbent, many investigators have been conducting research to develop a superior mixed metal oxide sorbent. [42][43][44][45][59][60][61][62][63] Earlier experimental studies that pioneered the use of mixed-metal oxides were performed at the Massachusetts Institute of Technology (MIT), [64][65][66] Research Triangle Institute (RTI), 67 68 Electrochem, 69 44,45 has shown that titanium oxide is a better alternative to iron oxide additives in terms of the higher stability of the titanates over the ferrite compounds of zinc, and their similar sulfidation equilibria. With zinc titanates, the sulfidation temperature has been shown to extend to 700 °C, and sintering of the ZnO was greatly reduced.…”
Section: Sorbent Developmentmentioning
confidence: 99%
“…58 Because of the apparent limitations of the zinc ferrite sorbent, many investigators have been conducting research to develop a superior mixed metal oxide sorbent. [42][43][44][45][59][60][61][62][63] Earlier experimental studies that pioneered the use of mixed-metal oxides were performed at the Massachusetts Institute of Technology (MIT), [64][65][66] Research Triangle Institute (RTI), 67 68 Electrochem, 69 44,45 has shown that titanium oxide is a better alternative to iron oxide additives in terms of the higher stability of the titanates over the ferrite compounds of zinc, and their similar sulfidation equilibria. With zinc titanates, the sulfidation temperature has been shown to extend to 700 °C, and sintering of the ZnO was greatly reduced.…”
Section: Sorbent Developmentmentioning
confidence: 99%
“…Thus, the hot coal gas ($800-900°C) has to be cooled down to ambient temperature for sulfur removal and then heated up to a required temperature for burning in gas turbine [3]. To improve the thermal efficiency and lower the capital costs of IGCC system, solid sorbents, such as Fe 2 O 3 [4], CuO [5], and MnO x [6], which can adsorb H 2 S at high temperature, would be a better option for hot coal gas desulphurization.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, a deactivation model is proposed with the following assumptions: isothermal condition, pseudo-steady-state condition, first-order deactivation of the absorbent with respect to the solid surface which can be described in terms of an exponential decrease with time in its available surface, and constant activity throughout the surface of absorbent. The combined equation of mole balance and rate law for the packed bed reactor is given below: (6) The boundary conditions at inlet concentrations are At t=0 , C H2S =C H2Sin At t=t, C H 2 S =C H 2 Sout Therefore, (7) The first order exponential decay is a(t)=e k d t , substituting Eq. (6) to Eq.…”
Section: Deactivation Model For Ceo 2 Absorbentmentioning
confidence: 99%
“…ZnO has the most favorable thermodynamics for H 2 S removal among sorbents that have been investigated. However, despite its attractive thermodynamic properties, the reduction of ZnO and subsequent vaporization of elemental zinc create a serious problem over many cycles of sulfidation/regeneration at high temperatures [6,7]. As a result, alternate absorbents to minimize ZnO problems at high temperature ranges are needed.…”
Section: Introductionmentioning
confidence: 99%